GENDER AND POWER: WOMEN’S REPRESENTATION IN ELECTORAL POLITICS - Chachane, Harsha (International Journal of Research -GRANTHAALAYAH, 2025)
Gender inequality in political representation remains a global challenge, particularly in developing democracies where patriarchal norms, socio-economic constraints, and institutional biases restrict women’s participation. This research investigates the relationship between gender representation, political empowerment, and governance quality using a political sociology and institutional lens. Hypothetical comparative data from 10 countries indicate that increased women’s representation correlates positively with governance transparency, social equity policies, and voter participation. Despite global advancements, the study reveals persistent structural barriers such as gender bias in party nominations and campaign financing. The paper concludes that institutional reforms, inclusive party systems, and targeted gender quotas can accelerate gender parity in political leadership.